A educação sexual no Amapá: experiências e desafios docentes - Pantoja, Florinaldo Carreteiro (2013)
This study portrays pedagogical experiences of the teacher facing sex education, with emphasis on the difficulties of implementing the theme in the classroom, as well as the experience in the process of mainstreaming. Sex education is a complex issue that has many variables that complicate their work, among them the very complexity of the subject, moral and religious concepts socially imposed, the little family participation in the process, the neglect of the educational institutions in the inclusion and deepening of theme in training, content that dominates the classrooms and inadequate continuing education. Our argument is that years have passed the law creating the guidelines and bases of education and the national curriculum guidelines, and teachers have failed to implement in their practice teaching sexual content, and the main cause is the deficiency in teacher training, for the few theoretical data do not allow teachers to implement this practice. The objectives were to know, record, and understand the conceptions of sexual education, prevailing among public school educators, elementary school, in the city of Macapá/AP, highlight the training of teachers investigated, from school age to work and relate sex education, investigate how the performance of teachers, possible difficulties with the cross-cutting and interdisciplinarity, as do the relationship of their discipline with sex education; understand the family\'s participation in the process of sex education on the point of view teacher; highlight the participation of health programs in the process of sex education in schools. Studying sex education in its general aspects it is still a challenge in academia. Scientific publications, have intensified through researchers and scholars in the field as: Ribeiro (1990), Sayão (1997), Vitiello (2000), Altman (2001), Dourado (2002), Furlani (2003), Fazenda (2005), Nunes e Silva (2006), Louro (2008), Stearns (2010); however, the literature on specific training , Figueiró (2006 ) is one of the few who study the subject in Brazil . This study deals with a qualitative descriptive approach, using the interview as a technique for data collection, 20 subjects were investigated, 18 teachers and 02 administrators of health programs, the research was conducted in the city of Macapá /AP, in a public school in reference works of sexuality as a technique of data analysis used the content analysis of Bardin(2004). In summary the results show that the training of these teachers to the thematic sexuality was very superficial both in primary and secondary education and professional experience, professional practice , appear as major difficulties need to work the \"self\" sexual teacher , unprepared manager on the issue , and lack of family support in the process. About their experiences, show that the thematic working within the school brings practical results as reducing teen pregnancy in school, and the lack of this experience coma theme is a factor that contributes to insecurity and the neglect of the subject. In their conception of the national curriculum guidelines, interdisciplinarity and transversal, the data showed a gap of teachers with these issues and to some ignorance because they know they exist but cannot set them. The family appears as an important variable and paramount in this process, and there should be greater dialogue and approach with the school since about health programs in schools, there is no such integration between health and education programs for the proposal, although not being a reality health professionals within the school.